A Developmental Pathway From Early Life Stress to Inflammation: The Role of Negative Health Behaviors. (June 2014) - Raposa, Elizabeth B.; Bower, Julienne E.; Hammen, Constance L.; Najman, Jake M.; Brennan, Patricia A.
Early life stressors are associated with elevated inflammation, a key physiological risk factor for disease. However, the mechanisms by which early stress leads to inflammation remain largely unknown. Using a longitudinal data set, we examined smoking, alcohol consumption, and body mass index (BMI) as health-behavior pathways by which early adversity might lead to inflammation during young adulthood. Contemporaneously measured early adversity predicted increased BMI and smoking but not alcohol consumption, and these effects were partially accounted for by chronic stress in young adulthood. Higher BMI in turn predicted higher levels of soluble tumor necrosis factor receptor type II (sTNF-RII) and C-reactive protein (CRP), and smoking predicted elevated sTNF-RII. These findings establish that early adversity contributes to inflammation in part through ongoing stress and maladaptive health behavior. Given that maladaptive health behaviors portend inflammation in young adulthood, they serve as promising targets for interventions designed to prevent the negative consequences of early adversity.